THE ROLE OF INTERPERSONAL AND FIRM FACTORS IN INTERNATIONAL BUSINESS RELATIONSHIPS - Farid Ahmed (Asian Academy of Management Journal, 2010)
Managers have long known intuitively that relationships are important to business. In certain cultures, such as in the East, the emphasis on relationships may typically be more explicit, but a good salesperson knows that building trust and commitment with buyers are essential for long-term success. The role of interpersonal and firm factors on international business relationships are tested with data from 125 pairs of exporter-importer relationships. Drawing from relational exchange theory, personal (such as effective communication, cultural sensitivity and likability of partner) and firm (such as reputation and competencies of partner) factors are modeled as determinants of commitment and trust in such relationships. The findings support the overall model, highlighting the importance of interpersonal and firm factors to international business relationships. This research highlights the importance of personal and organisational factors that are linked to building trust and commitment. In particular, building, protecting and communicating a positive reputation, and ensuring strong marketing competencies, are important for building contractual and competence trust. The study highlights the importance of interpersonal factors and thus the need to have appropriate personnel involved in the developing and maintaining international business relationships.